2023
DOI: 10.1038/s41598-023-32644-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of high proprotein convertase subtilisin/kexin type 9 antibody level with poor prognosis in patients with diabetes: a prospective study

Abstract: In addition to pathogenic autoantibodies, polyclonal autoantibodies with unknown physiological roles and pathogenicity are produced in the body. Moreover, serum antibodies against the proprotein convertase subtilisin/kexin type 9 (PCSK9) protein, which is integral to cholesterol metabolism, have also been observed. PCSK9 was also reported to be associated with insulin secretion and diabetes mellitus (DM). Therefore, we aimed to examine the clinical significance of PCSK9 antibodies (PCSK9-Abs) levels. We measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…After 48 months, it was observed that Evolocumab effectively brought down LDL-C to an average of 30 mg/dL which was sustained in subsequent studies. Although a recent clinical study argued that after examining all potential confounding factors, higher levels of anti-PCSK9 autoantibodies were significantly related to the increased deaths among diabetes patients, 451 Evolocumab has been reported to significantly decrease the risk of recurring CVEs in patients with pre-existing ASCVD and/or T2D. 452 , 453 The relative risk (RR) for the main outcome reduced by 15%, with a HR of 0.85 (95% CI 0.79–0.92) over a median 2.2-year monitoring period.…”
Section: Pcsk9 As a Potential Target For Multiple Disordersmentioning
confidence: 99%
“…After 48 months, it was observed that Evolocumab effectively brought down LDL-C to an average of 30 mg/dL which was sustained in subsequent studies. Although a recent clinical study argued that after examining all potential confounding factors, higher levels of anti-PCSK9 autoantibodies were significantly related to the increased deaths among diabetes patients, 451 Evolocumab has been reported to significantly decrease the risk of recurring CVEs in patients with pre-existing ASCVD and/or T2D. 452 , 453 The relative risk (RR) for the main outcome reduced by 15%, with a HR of 0.85 (95% CI 0.79–0.92) over a median 2.2-year monitoring period.…”
Section: Pcsk9 As a Potential Target For Multiple Disordersmentioning
confidence: 99%
“…In terms of biomarker species, studies have reported enzyme, antigen, and, in recent years, nucleotide markers ( 1-3 ). However, there are still some reports on antibody markers, which include heat-shock 60-kD protein 1( 4 ), replication protein A2( 5 ), programmed cell death 11( 6 ), metalloproteinase 1, chromobox homolog 1, chromobox homolog 5( 7 ), DnaJ heat shock protein family (Hsp40) member C2( 8 ), adaptor-related protein complex 3 subunit delta 1( 9 ), serpin peptidase inhibitor, clade E member 1( 10 ), death-inducer obliterator 1, cleavage and polyadenylation specificity factor 2, forkhead box J2( 11 ) and thiosulfate sulfurtransferase-like domain-containing 2( 12 ) for acute ischemic stroke (AIS); ATPase, Ca ++ transporting, plasma membrane 4( 10 ), bone morphogenetic protein 1 ( 3 , 13 ), deoxyhypusine synthase ( 14 ), SH3 domain-binding protein 5( 15 ), prolyl carboxypeptidase ( 16 ), low-density lipoprotein receptor-related protein-associated protein 1( 17 ) and additional sex combs-like 2( 18 ) for atherosclerosis; nardilysin ( 19 ) for acute cardiac syndrome; and insulin ( 20 ), glutamic acid decarboxylase ( 21 ), adiponectin ( 22 ) and growth arrest and DNA-damage-inducible gene 34 ( 23 , 24 ), and proprotein convertase subtilisin/kexin type 9( 25 ) for diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%